Spanish and Portuguese across time, place, and borders studies in honor of milton M. Azevedo - Callahan, Laura; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Spanish and Portuguese Across Time covers a diverse range of topics with a common focus, on the dynamic nature of languages and the social forces that shape them across time, place, and borders, and demonstrates how linguistic principles can offer productive angles to the study of literature.
Keywords: Linguistics; Literature -- Translations; Romance languages; Sociolinguistics; Translation and interpretation; Linguistics; Sociolinguistics; Translation; Romance Languages; Translation Studies